An adaptive-learning approach to affect regulation: strategic influences on evaluative priming - Freytag, Peter; Blümke, Matthias; Fiedler, Klaus (Cognition & emotion, 2011)
An adaptive cognition approach to evaluative priming is not compatible with the view that the entire process is automatically determined by prime stimulus valence alone. In addition to the evaluative congruity of individual prime-target pairs, an adaptive regulation function should be sensitive to the base rates of positive and negative stimuli as well as to the perceived contingency between prime and target valence. The present study was particularly concerned with pseudocontingent inferences that offer a proxy for the assessment of contingencies from degraded or incomplete stimulus input. As expected, response latencies were shorter for the more prevalent target valence and for evaluatively congruent trials. However, crucially, the congruity effect was eliminated and overridden by pseudocontingencies inferred from the stimulus environment. These strategic inferences were further enhanced when the task called for the evaluation of both prime stimuli and target stimuli.
Gesehen am 20.04.2023